2003
DOI: 10.1152/ajpcell.00076.2003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of the minimal promoter region of the human thiamin transporter SLC19A2

Abstract: The molecular mechanisms involved in the regulation of thiamin transport in mammalian cells are poorly understood. Previous studies established that a human thiamin transporter, SLC19A2, plays a role in thiamin uptake in human tissues. We cloned the 5' regulatory region of the SLC19A2 gene, identified the minimal promoter required for basal activity, and located multiple putative cis elements. To further characterize the SLC19A2 promoter, we investigated, in the present study, the role of the putative cis elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 21 publications
1
71
0
Order By: Relevance
“…These findings, however, do not eliminate the possibility that other cisand trans-acting elements may also contribute to minimal promoter activity. Previously, we (27) have shown that the minimal promoter region of the other thiamin transporter SLC19A2 contains several cis-regulatory elements important for promoter activity, including SP1. In this regard, it is interesting to note that SP1 is involved in the regulation of basal promoter activity of both thiamin transporters, and thus this NF appears be important for regulation of both thiamin transporter genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings, however, do not eliminate the possibility that other cisand trans-acting elements may also contribute to minimal promoter activity. Previously, we (27) have shown that the minimal promoter region of the other thiamin transporter SLC19A2 contains several cis-regulatory elements important for promoter activity, including SP1. In this regard, it is interesting to note that SP1 is involved in the regulation of basal promoter activity of both thiamin transporters, and thus this NF appears be important for regulation of both thiamin transporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…With this knowledge in mind and because expression of these two hTHTRs is tissue/ cell specific (9,26,27), understanding the basal and regulated transcriptional activity of the involved genes is obviously important. To achieve this aim, we have recently cloned the 5Ј-regulatory region of the human SLC19A2 gene and confirmed its promoter activity first in vitro and then in vivo using transgenic mice (26,27). In addition, we have identified the minimal region required for basal activity of the SLC19A2 promoter and identified a role of cis-regulatory elements for gut-enriched Krupple-like factor, nuclear factor-1 (NF1), and stimulating protein-1 (SP1) in the regulation of the promoter activity and confirmed the promoter activity in vivo using transgenic mice.…”
Section: Slc19a3; Thiamin Transporter; Transcriptional Regulationmentioning
confidence: 99%
See 3 more Smart Citations